Circulating resistin is a significant predictor of mortality independently from cardiovascular comorbidities in elderly, non-diabetic subjects with chronic kidney disease. (2nd January 2016) - Marouga, Anna; Dalamaga, Maria; Kastania, Anastasia N.; Kroupis, Christos; Lagiou, Maria; Saounatsou, Koralia; Dimas, Kleanthi; Vlahakos, Demetrios V.
Abstract: Context : Resistin is associated with inflammation, atherosclerosis and cardiovascular (CV) disease. Objective : To associate circulating resistin with all-cause and CV mortality in chronic kidney disease (CKD) patients. Methods : Serum resistin was determined in a cohort of 80 elderly, non-diabetic patients with stable CKD at different stages in a follow-up period of 5 years. Results : Circulating resistin was significantly elevated in deceased compared to alive patients. Resistin emerged as an independent biomarker of all-cause and CV mortality after a 5-year follow-up period. Conclusion : Elevated circulating resistin was a significant independent predictor of CV and all-cause mortality in elderly, non-diabetic CKD patients.